ANALISIS KOMPETENSI MANTRI PT BANK RAKYAT INDONESIA (PERSERO) TBK, UNIT TODDOPULI MAKASSAR - Megawaty Megawaty (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The purpose of this study was to analyze the competencies required by a paramedic at PT. Bank Rakyat Indonesia (Persero) Tbk, Unit Toddopuli. The analysis of the data used is descriptive analysis of qualitative interviewing and analysis of the validity of the technique of triangulation. The analysis showed that qualification hard competencies in particular knowledge relating to credit ma uta is not to become a paramedic. Where in the recruitment of candidates registered BRI not see from his educational background, knowledge of the credit, but the psychological tests that look at the behavior of candidates registered or see the soft side competenciesnya. Pengetahuaan of credit will be in the can after being orderly given by BRI through education. So most of competence possessed by a paramedic at PT. Bank Rakyat Indonesia (Persero) Tbk, Unit Toddopuli is behavioral requirements. Behavior (attitude) is something that reflects the person. As for pengatahuan and sense of businessnya will evolve as work experience.